2019
DOI: 10.1155/2019/4714781
|View full text |Cite
|
Sign up to set email alerts
|

Cancer as an Embryological Phenomenon and Its Developmental Pathways: A Hypothesis regarding the Contribution of the Noncanonical Wnt Pathway

Abstract: For gastrulation to occur in human embryos, a mechanism that simultaneously regulates many different processes, such as cell differentiation, proliferation, migration, and invasion, is required to consistently and effectively create a human being during embryonic morphogenesis. The striking similarities in the processes of cancer and gastrulation have prompted speculation regarding the developmental pathways involved in their regulation. One of the fundamental requirements for the developmental pathways in gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 196 publications
(206 reference statements)
0
5
0
Order By: Relevance
“…Numerous previous studies, dating as far back as 1858 (Virchow's embryonal rest hypothesis), have observed parallels between cancer and development (55)(56)(57), proposing that cancer initiating cells are stuck at an earlier undifferentiated precursor developmental stage of the respective cell type, with activated immune suppressive and mesenchymal gene programs characteristic of early development (57). This would suggest that genes with perturbed expression in cancer are likely to be involved in tissue development and function.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous previous studies, dating as far back as 1858 (Virchow's embryonal rest hypothesis), have observed parallels between cancer and development (55)(56)(57), proposing that cancer initiating cells are stuck at an earlier undifferentiated precursor developmental stage of the respective cell type, with activated immune suppressive and mesenchymal gene programs characteristic of early development (57). This would suggest that genes with perturbed expression in cancer are likely to be involved in tissue development and function.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous previous studies, dating as far back as 1858 (Virchow's embryonal rest hypothesis), have observed parallels between cancer and development [57][58][59], proposing that cancer initiating cells are stuck at an earlier undifferentiated precursor developmental stage of the respective cell type, with activated immune suppressive and mesenchymal gene programs characteristic of early development [59]. This would suggest that genes with perturbed expression in cancer are likely to be involved in tissue development and function.…”
Section: Discussionmentioning
confidence: 99%
“…The zinc-finger transcription factors GATA4, which play important roles in BC progression from an early stage, and GATA6, which is overexpressed in BC and promotes BC cell epithelial-mesenchymal transition (EMT) [64] are essential for embryonic development during gastrulation [65]. Cofre et al (2019) showed that both developmental pathways in gastrulation and cancer require the ability to respond to environmental stimuli [66]. Thus, the Wnt signaling pathway has been reported to be highly conserved in metazoan animals and to play a critical role in controlling embryo and organ development, as well as in BC cells transformation, where its alterations have been correlated with mutations, amplifications, deletions, DNA methylation, and post-translational modification of proteins (PTMs) [67].…”
Section: Bc Is a Developmental Disordermentioning
confidence: 99%